Odd Riemannian symmetric spaces associated to four-forms - Cortés, Vicente (MATHEMATICA SCANDINAVICA, 2006)
To any four-form Ω satisfying certain system of quadratic equations a Lie superalgebra g = g_0 + g_1 endowed with an invariant scalar superproduct is associated. The geometric structure of the corresponding odd symmetric superspace, which is of hyper-Kähler type, is described. Finally, some classes of solutions to the quadratic system are discussed.